Lichens and Rocks: A Review - Easton, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1994)
Summary Lichens, especially saxicolous (rock-in-habiting) lichens, are encountered almost daily by the field geologist. Despite the difficulties in readily identifying lichens, there is increasing evidence that many species have a preference for some rock types, and that certain species can chemically modify their substrate. There is also increasing evidence that certain lichens, some of which change colour based on absorbed metal content, may make effective indicator plants in mineral exploration, particularly in areas such as the Northwest Territories.